The double closet: Mental health needs of LGB college students from an intersectional perspective - Athenai Ximena Sánchez-Millán; Marcela Tiburcio-Sainz; María Asunción Lara-Cantú; Tania Esmeralda Rocha-Sánchez (PLoS ONE, 2025)
College is a crucial stage for personal development and can be particularly challenging for lesbian, gay, and bisexual (LGB) students as they face unique challenges related to their sexual orientation as well as social barriers. This qualitative study aimed to explore the mental health needs of LGB university students from an intersectional perspective. Twelve semi-structured interviews were conducted with seven bisexual, two homosexual, and three lesbian students at a public university in the state of Puebla. Content analysis with an intersectional perspective was used to explore their experiences to capture the factors affecting their mental health needs, from what leads them to seek mental health services to the moment they receive care and how that experience affects various areas of their lives. The findings suggest that LGB students often live in a “double closet,” concealing both their sexual orientation and their mental health, primarily from their families. From a university perspective, exploring this issue provides a framework for future interventions designed to address intersectional stigma in universities, through actions such as awareness-raising workshops and visual materials to create an inclusive environment and raise awareness about this issue and its consequences.